2011
DOI: 10.1371/journal.pone.0027697
|View full text |Cite
|
Sign up to set email alerts
|

The Colonization History of Juniperus brevifolia (Cupressaceae) in the Azores Islands

Abstract: BackgroundA central aim of island biogeography is to understand the colonization history of insular species using current distributions, fossil records and genetic diversity. Here, we analyze five plastid DNA regions of the endangered Juniperus brevifolia, which is endemic to the Azores archipelago.Methodology/Principal FindingsThe phylogeny of the section Juniperus and the phylogeographic analyses of J. brevifolia based on the coalescence theory of allele (plastid) diversity suggest that: (1) a single introdu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
46
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(55 citation statements)
references
References 77 publications
9
46
0
Order By: Relevance
“…In a recent study of Silva et al (2011) it was identified a high degree of differentiation and restricted gene flow between populations, which contradicts the accepted theories for the Azorean plant diversity with low number of radiations and low number of single-island endemics and also contradicts the life traits of this species that favours the long distance dispersal, colonization and gene flow exchange (Carine and Schaefer, 2010;Rumeu et al, 2011a;Schaefer et al, 2011).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…In a recent study of Silva et al (2011) it was identified a high degree of differentiation and restricted gene flow between populations, which contradicts the accepted theories for the Azorean plant diversity with low number of radiations and low number of single-island endemics and also contradicts the life traits of this species that favours the long distance dispersal, colonization and gene flow exchange (Carine and Schaefer, 2010;Rumeu et al, 2011a;Schaefer et al, 2011).…”
Section: Introductionmentioning
confidence: 88%
“…The presence of J. brevifolia in the Azores implies one of the most remote juniper colonization known (Rumeu et al, 2011a), representing one of the best examples of endemic species displaying traits favourable for long-distance dispersal and colonization, i.e. dioecy, anemophily, zoochory, multi-seeded cone (Adams, 2011) and mesic habitats requirements (Elias, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…However, the islands are located over a complex microplate rather than a single hotspot. Nevertheless, there is some evidence for a directional mode of dispersal from older to younger islands [plants (80,81); arthropods (82,83)], although a simple progression rule is not common [yet Van Riel (84) presents intriguing evidence from gastropods]. Much of the current evidence consists of age estimates of haplotypes/alleles rather than robustly structured cladogenetic branching between islands.…”
Section: The Progression Rule In Comparative Island Phylogeographymentioning
confidence: 99%
“…Genetic diversity of Juniperus species has been most extensively examined by RAPDs (Adams & Demeke, 1993;Adams et al, 2003;Adams, 2011;Dzialuk et al, 2011;Kasaian et al, 2011) in comparison to other molecular markers like microsatellites (Provan, 2008;Michalczyk et al, 2006;Douaihy et al, 2011;Sobierajska et al, 2016) or Amplified Fragment Length Polymorphism (Van der Merwe et al, 2000;Rumeu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%